Dysregulation of the Immune Environment in the Airways During HIV Infection - Bunjun, Rubina; Soares, Andreia P.; Thawer, Narjis; Müller, Tracey L.; Kiravu, Agano; Ginbot, Zekarias; Corleis, Björn; Murugan, Brandon D.; Kwon, Douglas S.; von Groote-Bidlingmaier, Florian; Riou, Catherine; Wilkinson, Robert J.; et al. (Frontiers in Immunology, 2021)
HIV-1 increases susceptibility to pulmonary infection and disease, suggesting pathogenesis in the lung. However, the lung immune environment during HIV infection remains poorly characterized. This study examined T cell activation and the cytokine milieu in paired bronchoalveolar lavage (BAL) and blood from 36 HIV-uninfected and 32 HIV-infected participants. Concentrations of 27 cytokines were measured by Luminex, and T cells were phenotyped by flow cytometry. Blood and BAL had distinct cytokine profiles (p=0.001). In plasma, concentrations of inflammatory cytokines like IFN-γ (p=0.004) and TNF-α (p=0.004) were elevated during HIV infection, as expected. Conversely, BAL cytokine concentrations were similar in HIV-infected and uninfected individuals, despite high BAL viral loads (VL; median 48,000 copies/ml epithelial lining fluid). HIV-infected individuals had greater numbers of T cells in BAL compared to uninfected individuals (p=0.007); and BAL VL positively associated with CD4+ and CD8+ T cell numbers (p=0.006 and p=0.0002, respectively) and CXCL10 concentrations (p=0.02). BAL T cells were highly activated in HIV-infected individuals, with nearly 2-3 fold greater frequencies of CD4+CD38+ (1.8-fold; p=0.007), CD4+CD38+HLA-DR+ (1.9-fold; p=0.0006), CD8+CD38+ (2.8-fold; p=0.0006), CD8+HLA-DR+ (2-fold; p=0.022) and CD8+CD38+HLA-DR+ (3.6-fold; p<0.0001) cells compared to HIV-uninfected individuals. Overall, this study demonstrates a clear disruption of the pulmonary immune environment during HIV infection, with readily detectable virus and activated T lymphocytes, which may be driven to accumulate by local chemokines.